The structure of health in Europe: The relationships between morbidity, functional limitation, and subjective health - Aija Duntava; Liubov V. Borisova; Ilkka Henrik Mäkinen (Elsevier, 2021)
The main objective of this study is to explore the relationships between the three commonly used proxies of health, morbidity, functional limitation, and subjective health, using the most recent data from 18 European countries. The existing studies on the topic are outdated, limited to the United States and to elderly population. Data on 32,679 respondents of the European Social Survey (2014) were analyzed using structural equation modeling. The results suggest that (a) morbidity and functional limitation lead to poorer self-rated health, and (b) morbidity increases the probability of reporting functional limitation(s). Moreover, functional limitation mediates the relationship between morbidity and self-rated health. The model as a whole holds across both genders and all age groups. However, specific tests (SEM multi-group analyses, t-tests) show differences in the health structure between all seven subsamples compared with each other. When both gender and age are taken into account the differences in the structure of health seem to diminish, apart from the elderly, suggesting that the health structure of the elderly differs from others. It is recommended for policy planners to acknowledge the group differences when shaping the policies and health services.